PERANAN KEPUASAN KONSUMEN DALAM MEMODERASI PENGARUH KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA UMKM D’PORE MEME DI SITUBONDO - Musleha, Ummi Rohmatil; Pramitasari, Triska Dewi; Soeliha, Siti (Fakultas Ekonomi dan Bisnis, 2025)
UMKM D’pore Meme has an important role in developing work processes, encouraging innovation and providing comprehensive contributions to economic growth. The purpose of this study was to determine the effect of the Brand Image, Product Quality, and Service Quality on purchasing decisions through Consumer Satisfaction as a moderating variable at UMKM D’pore Meme in Situbondo. The population in this study was consumers of UMKM D’pore meme in Situbondo. The sampling technique was determined by purposive sampling. The data analysis and hypothesis testing in this study used the Smart PLS 3.0 application. The results of the direct influence hypothesis test show that the Brand image strengthens the relationship significantly positive to Purchase Decisions, the Product Quality strengthens the relationship significantly positive to Purchase Decisions, the Service Quality weakens the relationship positively to Purchase Decisions, and the Consumer Satisfaction weakens the relationship negatively to the role of Service Quality in increasing Purchase Decisions.